First Report of Cassytha filiformis Parasitizing Justicia gendarussa in Malaysia - Khoo, Ying Wei; Li, Shifang; Chong, Khim Phin (Springer Nature, 2022)
‘Gandarusa’ (Justicia gendarussa, family Acanthaceae) is an evergreen shrub. Its leaves and stem extracts are used for antiangiogenis, anticancer, antimicrobial, antioxidant and hepatoprotective purposes. In July 2021, sign of haustoria of the parasitic plant attached on estimated 50% of ‘Gandarusa’ with leaf yellowing symptoms was observed in a park (50 m2 site of investigation) of Universiti Malaysia Sabah (UMS), Sabah, Malaysia (6°01’55.6"N 116°07’18.5"E).